Collaborative research stories : whakawhanaungatanga - Bishop, Russell, 1950- (NZAM academic monograph ;, 1996)
This thesis seeks to acknowledge and address the concerns that Maori people voice about research into their lives. The present study shows that Maori people are concerned that the power and control over research issues of initiation, benefits, representation, legitimation and accountability are addressed by the imposition of the researcher's agenda, concerns and interests on the research process. Such dominance of a Western orientated discourse is being challenged by a pro-active, Kaupapa Maori research approach. This approach is part of the revitalisation of Maori cultural aspirations, preferences and practices as a philosophical and productive educational stance and resistance to the hegemony of the dominant discourse in Aotearoa/New Zealand.